Applications of graphene nanoplatelets as working fluids in photovoltaic thermal systems: A review - Muhamed Rafaizul, Nurul Izzati Akmal; Mohd Rosli, Mohd Afzanizam; Salimen, Nurfarhana; Habibi, Ilham Akbar; Permanasari, Avita Ayu; Herawan, Safarudin Gazali (Universiti Malaysia Perlis, 2024)
The application of nanofluids, specifically graphene nanoplatelets, as a working fluid in photovoltaic thermal (PV/T) has attracted much attention due to the enhanced thermophysical properties of nanofluids compared to those of conventional working fluids. In comparison to traditional fluids, nanofluid is a potential heat transfer fluid that can significantly improve system efficiency. The nanoparticle's large surface area and small size result in an increased rate of heat transmission. This review addressed the use of graphene nanoplatelets (GNP) as a working fluid in PV/T systems. Incorporating GNP into PV/T systems can attain many advantages, including enhanced thermal conductivity and increased energy conversion efficiency. The review goes through the difficulties in synthesizing and characterizing GNP and the thermophysical properties of GNP. In addition, the review highlights the experimentation on the performance of PV/T systems in terms of thermal properties that use GNP as their working fluid. The integration of graphene nanoplatelets (GNP) as a working fluid in photovoltaic thermal (PV/T) systems holds immense promise for enhancing system efficiency and energy conversion rates. The demonstrated benefits of GNP, including its superior thermal conductivity and increased heat transmission efficiency, underscore its potential as a key component in advancing PV/T technology. The reviews concluded that the composition of 0.5 wt.% with a ratio of 1:1 to the surfactant shows the best formulation and can achieve good dispersion of the nanofluid.